Sukarno's Thought about Marhaenism - Aminuddin Aminuddin; Katimin Katimin; Syukri Syukri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Marhaenism is a pure thought sparked by Soekarno which departs from the most substantial and universal human life needs, namely the Social Conventions of Man, which requires the realization of the welfare of human life that can only be fulfilled if the harmonization between individual independence and social justice has been created. In reality these demands could not be found at the time, and this concern over the problems (the fate of the Indonesian nation) was the starting point of Sukarno's study in giving perspective to the ideology of marhaenism. This group of poor and destitute people is what Soekarno called the Marhaen.